Disasters and politics materials, experiments, preparedness - Tironi Rodó, Manuel; Rodriguez-Giralt, Israel; Guggenheim, Michael (Wiley Blackwell/The Sociological Review, 2014)
"Arguing that disasters configure the political in new ways, this collection provides a truly international insight into how they can help us to understand the materiality and the pragmatics of politics. As events of radical disruption, disasters can also lead to a re-evaluation of the very definition of the political itself. In exploring these issues, the collection brings together disaster studies, with political theory and science and technology studies, to stimulate a more robust conversation between disciplines and feed into broader sociological debates. Takes an innovative approach to the relationship between disasters and the nature, composition, and effects of the political Leading experts scrutinize how events of radical disruption enable a re-evaluation and redefinition of the political, and the tools and processes through which this happens Comparative case studies give an unrivaled geographic scope, covering Australia, Europe, South America, and the United Kingdom and United States Brings together disaster studies, political theory, and science and technology studies to stimulate broader sociological debate Combines empirical and theoretical approaches to provide an essential teaching resource for graduate and postgraduate students and to open up this dynamic field for mainstream sociology researchers and academics "--